Respostas
respondido por:
1
Resolução:
( x - 1)² - 16 = 0
( x - 1)² = 16
x - 1 ± 4
x - 1 = 4
x - 1 = -4
x = 5
x = -3
x € R
( x - 1)² - 16 = 0
( x - 1)² = 16
x - 1 ± 4
x - 1 = 4
x - 1 = -4
x = 5
x = -3
x € R
respondido por:
1
(x-1)²-16=0
x²+2*x*-1+ (-1)²=16
x²-2x+1-16=0
x²-2x-15=0
delta=b²-4ac
2²-4*1*-15
4+60
=64
x1= (-b+8)/2
x1=10/2=5
x2=(-b-8)/2
x2=-6/2=-3
x²+2*x*-1+ (-1)²=16
x²-2x+1-16=0
x²-2x-15=0
delta=b²-4ac
2²-4*1*-15
4+60
=64
x1= (-b+8)/2
x1=10/2=5
x2=(-b-8)/2
x2=-6/2=-3
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás